Influence of relative luminance and angle between movement directions of two moving stimuli on direction detecting - Šatinskas, Romualdas; Pleskačiauskas, Aleksandras; Stabinytė, Dalia; Vaitkevičius, Henrikas (Psichologija, 2001)
The goal of the present research was to investigate the perception of movement direction. The main purpose was to detect if the mix of directions was present and ascertain the mechanism of this process. We carried out 35 psychophysical experiments with 6 observers. Two bright stimuli moved on a screen with different angle between movement directions or with different brightness of the stimuli. The results showed that perceived direction of movement was attracted to the second stimulus trajectory if the angle between trajectories was less than 90 degrees. And this phenomenon was the stronger the brighter the second stimulus was. When the angle was more than 90 degrees the effect of pushing was observed. While the distance between stimuli is comparatively little the attraction prevails as it is caused by the summation and averaging of signals within a single receptive field of a neuron. When the distance between stimuli grows the effect of pushing is observed because of the lateral inhibition amongst the different channels of movement analysis. These results show that a process of mix of directions is present in perception of movement direction and are strong factors in proving the vectorial model of movement perception.